CORREÇÃO DE ERRO, ATENÇÃO E NOTICING: RELEVÂNCIA PARA A SALA DE AULA - Azeredo, Flávia; de Mello, Heliana Ribeiro (Organon, 2011)
Second language acquisition studies have claimed that feed-back, in the form of recasts, has a positive impact on learners’ L2 develop-ment. " is study aims to examine the e# ectiveness of two corrective feed-back forms, recasts and models, on Brazilian learners of English acquiringtwo language structures and the role of focus attention and noticing inthis scenario. " e present research was conducted with thirty-three stu-dents randomly selected to perform two communicative activities in threedi# erent sessions. During the activities, the participants received correc-tive feedback according to the experimental condition they were assigned." e participants were tested by means of grammaticality judgment testsand oral picture descriptions. Along with the language activities, the par-ticipants also performed attention control tests and a stimulated recalltest. " e results suggest that recasts and models were more e# ective thanno feedback. As for the cognitive factors, the results showed a complexscenario. Overall, attention seems to be the most relevant component ofthe cognitive variables contemplated on this research.